ANALYSIS OF MURABAHAH AGREEMENT IMPLEMENTATION AT KSPPS NURI PASEAN BRANCH EAST JAVA - Samsul, Samsul; Marsidi, Marsidi; Bari, Abdul (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to comprehensively analyze the implementation of the murabahah contract as an effective financing alternative at KSPPS NURI East Java Pasean Branch and its contribution in supporting the economic growth of its members. The murabahah contract, which is one of the main products in Islamic finance, offers financing solutions that are in accordance with sharia principles. This study uses a qualitative descriptive approach with a case study method, where data is collected through in-depth interviews, observations, and documentation. The results of the study show that the implementation of the murabahah contract at KSPPS NURI East Java Pasean Branch is going well and has had a positive impact on improving the economy of members, especially in terms of the development of micro and small businesses. However, there are still challenges in terms of risk management and member education related to this contract. Therefore, further optimization strategies are needed to ensure sustainability and increased benefits for cooperative members.